Effect of treadmill exercise on pain-related Wnt/β-catenin signaling pathway in dorsal root ganglion neurons at the early phase regeneration of the injured sciatic nerve - Cho, Yeong-Hyun; Kim, Ji-Eun; Seo, Tae-Beom (Journal of exercise rehabilitation, 2021)
The purpose of this study was to determine whether treadmill walking exercise can improve mechanical allodynia through regulation of Wnt/β-catenin signaling in dorsal root ganglion (DRG) neurons at the early stage of regeneration after sciatic nerve injury (SNI). The experimental rats were divided into seven groups: the normal control, sedentary groups for 3-, 7-, and 14-day post crush (dpc), and exercise group for 3, 7, and 14 dpc. The rats in exercise groups performed treadmill walking exercise at a speed of 8 m/min for 20 min once a day according to ex-periment duration. For evaluating neuropathic pain-like behavior after SNI, the mechanical allodynia was examined by von Frey apparatus. And the expression levels of pain-related protein were identified in the cytoplasm or nucleus of DRG neurons using Western blot techniques. Mechanical allodynia was significantly ameliorated in the exercise group at 7 and 14 dpc. Treadmill exercise further decreased Wnt3a ex-pression at 3, 7, and 14 dpc compared to in the sedentary group. Also, phosphorylated-low-density lipoprotein receptor 6 was decreased in exercise groups at 3 and 14 dpc. Beta-catenin was significantly de-creased in exercise groups at 3 and 14 dpc compared to sedentary groups as well as treadmill exercise decreased translocation of β-cat-enin towards the nucleus of DRG neurons at 14 dpc. Our findings indi-cate that treadmill walking exercise may be an important regulator of neuropathic pain after peripheral nerve injury through delayed Wnt/β-catenin signaling pathway in DRG neurons.